SISTEM PENGATURAN PH AIR PADA AKUARIUM IKAN KOI MENGGUNAKAN FUZZY SUGENO - Muh. Ghiffari Caesa Ramadahan; n/a Rahmadwati; Eka Maulana (Jurnal Mahasiswa TEUB, 2022)
Koi is one of the largest contributors to ornamental fish exports based on data from the 2014-2018 KKP, koi exports have increased from 767 kg in 2017 to 2,162 kg. The high demand for koi encourages cultivators to increase their koi fish farmingbusiness. Koi live in freshwater waters with a pH ranging from 7.5 to 8.5 with a tolerance of 6-9 in calm water currents and have many aquatic plants. Continuous monitoring of water quality, especially pH levels, is very much needed. Monitoring the pH level of water in fish farming ponds is currently still done using the manual method, namely by measuring directly to the aquarium which takes a long time and is inefficient. So that this problem can be overcome, a pH control device in the aquarium is made that can monitor and control pH levels continuously in the aquarium. Controlling pH levels in aquarium water is done by giving a certain amount of acid (pH down) or alkaline (pH up) solution that can increase and decrease pH levels so that the pH in aquarium water is always stable in a predetermined range. The acid or base solution is sucked up by a water pump motor to be discharge